Growth and Development of Nanobiotechnology Applications and Future Prospects - Lutfi Khamees Alfirjani,; Ashraf A Naass,; Akarm Mansour Sherif,; Abdulfattah Elhady Abokridighaha, (AlQalam Journal of Medical and Applied Sciences, 2024)
Despite the high cost of nanomaterials and devices, nanotechnology is witnessing great growth and development worldwide, and competition has become great among developed countries to produce and develop this technology by allocating huge budgets and expanding the establishment and support of specialized research centers due to the increasing demand for it. This modern technology is considered the latest technology. What has been achieved by scientific and technological development in recent years, which would work to achieve the economic goals of comprehensive development through employing various economic resources and making optimal use of them. This study aimed to introduce nanotechnology, its importance and applications in various areas of life, and to clarify the extent of the possibility of benefiting from it in achieving the economic goals of comprehensive development. The study reached some results and recommendations, the most important of which is encouraging work on introducing and using nanotechnology as an entry point for comprehensive development in Libyan industry, especially industries that face high competition from imported products, and marketing environmentally friendly products in the local market as a first step through transferring the results of research and academic studies to industrial facilities and various production companies. Establishing, supporting and developing centers for nanotechnology research in Libya and linking them with regional and international organizations to benefit from their expertise in this field, Educating and encouraging the private industrial sector to use nanotechnology because of its great advantages and benefits to the environment and society, Also since oil is considered the primary source of income in Libya, which represents about 95% of the total GDP, if the state focuses on supporting and encouraging investment in the direction of using nanotechnology by exploiting and investing in the resources available to it, there is great potential to benefit from it as a source of income that provides It is an addition to Libya gross domestic product and is considered a source of diversified national income. بالرغم من التكلفة المرتفعة للمواد والأجهزة النانوية فإن تقنية النانو تشهد نمواً وتطوراً كبيرين على مستوى العالم وأصبحت المنافسة كبيرة بين الدول المتقدمة لإنتاج هذه التقنية وتطويرها من خلال تخصيص ميزانيات ضخمة والتوسع في إنشاء المراكز البحثية المتخصصة ودعمها بسبب الطلب المتزايد عليها ، و تعتبر هذه التقنية الحديثة أخر ما توصل إليه التطور العلمي والتكنولوجي خلال السنوات الاخيرة والتي من شأنها أن تعمل على تحقيق الأهداف الإقتصادية للتنمية المستدامة من خلال توظيف الموارد الاقتصادية المختلفة واستخدامها الاستخدام الأمثل . وقد هدفت هذه الدراسة الى التعريف بتقنية النانو وأهميتها وتطبيقاتها في مجالات الحياة المختلفة وتوضيح مدى إمكانية الإستفادة منها في تحقيق الأهداف الإقتصادية للتنمية المستدامة. وتوصلت الدراسة إلى بعض النتائج والتوصيات أهمها تشجيع العمل على إدخال وإستخدام تقنية النانو الحيوية كمدخل للتنمية المستدامة فى الصناعة الليبية وبخاصة الصناعات التي تواجه منافسة عالية من المستوردة وتسويق منتجات صديقة للبيئة فى السوق المحلي كخطوة أولى من خلال نقل نتائج البحوث والدراسات الأكاديمية إلى المنشآت الصناعية والشركات الإنتاجية المختلفة وإنشاء مراكز لأبحاث تقنية النانو في ليبيا ودعمها وتطويرها والربط بينها وبين المنظمات الإقليمية والدولية للإستفادة من خبراتها في هذا المجال ، و توعية وتشجيع القطاع الصناعي الخاص بإستخدام تقنية النانو الحيوية لما لها من ميزات وفوائد كبيرة على البيئة والمجتمع ، وكذلك بما أن النفط يعتبر المورد الوحيد للدخل في ليبيا والذي يمثل حوالي 95 % من إجمالي الناتج المحلي الإجمالي فإنه وفي حال ركزت الدولة على دعم وتشجيع الإستثمار في إتجاه إدخال واستخدام هذه التقنية ، فهناك إمكانية كبيرة للإستفادة منها كمورد دخل يقدم إضافة للناتج المحلي الإجمالي في ليبيا وتكون أحد مصادر تنوع الدخل